2006
DOI: 10.1111/j.1574-6968.2006.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

The arbuscular mycorrhizal fungal protein glomalin is a putative homolog of heat shock protein 60

Abstract: Work on glomalin-related soil protein produced by arbuscular mycorrhizal (AM) fungi (AMF) has been limited because of the unknown identity of the protein. A protein band cross-reactive with the glomalin-specific antibody MAb32B11 from the AM fungus Glomus intraradices was partially sequenced using tandem liquid chromatography-mass spectrometry. A 17 amino acid sequence showing similarity to heat shock protein 60 (hsp 60) was obtained. Based on degenerate PCR, a full-length cDNA of 1773 bp length encoding the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(71 citation statements)
references
References 44 publications
2
68
0
1
Order By: Relevance
“…Previous studies have shown that glomalin, a glycoprotein produced by AM fungi (Wright et al, 1996;Gadkar and Rillig, 2006;Rillig and Mummey, 2006), can binds metals, including Cu (González-Chávez et al, 2004;Cornejo et al, 2008;Meier et al, 2012c). This glycoprotein is distinguished by its extraction and detection methods (Wright et al, 1996;2006;Wright and Upadhyaya, 1998;Purin and Rillig, 2007) and has been quantified as a Bradford-reactive soil protein (BRSP; Rillig, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that glomalin, a glycoprotein produced by AM fungi (Wright et al, 1996;Gadkar and Rillig, 2006;Rillig and Mummey, 2006), can binds metals, including Cu (González-Chávez et al, 2004;Cornejo et al, 2008;Meier et al, 2012c). This glycoprotein is distinguished by its extraction and detection methods (Wright et al, 1996;2006;Wright and Upadhyaya, 1998;Purin and Rillig, 2007) and has been quantified as a Bradford-reactive soil protein (BRSP; Rillig, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These fungi deliver a variety of benefits to plants (e.g., increased nutrient uptake, improved water relations, protection from pathogens) in exchange for photosynthates (Newsham et al 1995). Arbuscular mycorrhizal fungi have been found to physically stabilize soil through the enmeshment of soil particles by filamentous hyphal networks and the production of glomalin, a putative heat-shock protein homolog (Gadkar and Rillig 2006), quantified in soils as operationally defined glomalin-related soil protein (GRSP; Wright and Upadhyaya 1996, Miller and Jastrow 2000, Rillig 2004. Glomalin is a component of the hyphal walls of AM fungi, which likely remains recalcitrant in soils following hyphal decomposition (Driver et al 2005, Gadkar andRillig 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi have been found to physically stabilize soil through the enmeshment of soil particles by filamentous hyphal networks and the production of glomalin, a putative heat-shock protein homolog (Gadkar and Rillig 2006), quantified in soils as operationally defined glomalin-related soil protein (GRSP; Wright and Upadhyaya 1996, Miller and Jastrow 2000, Rillig 2004. Glomalin is a component of the hyphal walls of AM fungi, which likely remains recalcitrant in soils following hyphal decomposition (Driver et al 2005, Gadkar andRillig 2006). Both hyphal density and GRSP concentration in soils have been found to be strongly correlated with aggregate stability in mesic soils (Wright and Upadhyaya 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the proteins will be glomalin-like proteins which relieve cells from stresses. Glomalin has been already known as glycoprotein weighs approximately 60 kDa [9], which has similarity to heat shock protein 60 [10].…”
Section: Discussionmentioning
confidence: 99%